2022
DOI: 10.34172/bi.2022.26386
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-immune cell therapy by intratumoral injection of adoptive NK cells with capecitabine in gastric cancer xenograft model

Abstract: Introduction: Gastric cancer is one of the most commonly known malignancies and is the fifth cancer-related death globally. Whereas natural killer (NK) cells play a critical role in tumor elimination; therefore, adoptive NK cell therapy has become a promising approach in cancer cytotherapy. Hence, this study investigated the chemo-immune cell therapy in MKN-45 derived xenograft gastric cancer model. Methods: Three groups of animals have received the following treatments separately: activated NK cells, capecita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Our research group demonstrated that pretreated checkpoint blockade NK cells could effectively enhance the NK cells’ trafficking in TME and beneficially reduce the tumor cell mitosis in gastric cancer xenograft model ( 189 ). However the same results was not achieved in chemo immune cell therapy of Intratumoral injection of NK cells in combination with capecitabine in gastric cancer xenograft model in the other study of our group ( 190 ).…”
Section: Antibodies Increase Nk Cell Cytotoxicity Against Colorectal ...mentioning
confidence: 48%
“…Our research group demonstrated that pretreated checkpoint blockade NK cells could effectively enhance the NK cells’ trafficking in TME and beneficially reduce the tumor cell mitosis in gastric cancer xenograft model ( 189 ). However the same results was not achieved in chemo immune cell therapy of Intratumoral injection of NK cells in combination with capecitabine in gastric cancer xenograft model in the other study of our group ( 190 ).…”
Section: Antibodies Increase Nk Cell Cytotoxicity Against Colorectal ...mentioning
confidence: 48%
“…Samples were then blocked with 5 μL human FcX block (cat#422302; 10 min). Following this, samples were stained (15 min) with the following flow cytometry antibodies: a lineage cocktail (anti-CD3, anti-CD14, anti-CD19), anti-CD16, and anti-CD56 ( Table 1 ) [ 10 , [17] , [18] , [19] , [20] , [21] ]. PBS was added to sample tubes for a final volume of 3 mL.…”
Section: Methodsmentioning
confidence: 99%
“… 6 Capecitabine, the first-line chemotherapeutic agent for CRC, has been shown to change the tumour microenvironment into an “immune-hot” subtype in patients, improve the antitumor effect of NK cells, and reduce myeloid-derived suppressor cells (MDSCs) ( Figure 1 ). 7 , 8
Figure 1 Augmentation of Immune Response through Oncolytic Viruses and Capecitabine Co-Therapy.
…”
Section: Introductionmentioning
confidence: 99%